Implementasi Online Assessment pada Mata Kuliah Pembelajaran Fiqih di IAINU Kebumen - Rita sulastini; Sri Handayani; Maesaroh Maesaroh (LPPM Institut Agam Islam Nahdlatul Ulama (IAINU) Kebumen, 2021)
This study aims to describe the implementation of online-based assessment in Fiqh Learning courses at IAINU Kebumen. The study was conducted on fifth semester PAI students at the Nahdatul Ulama Islamic Institute (IAINU) Kebumen. The data obtained in the form of Fiqh learning test results obtained through test techniques. Data analysis used an interactive model with the stages of data condensation, data presentation, and drawing conclusions. The results showed that the planning stage included competency and indicator analysis activities through RPS, selection of test forms and online media, preparation of questions, preparation of exam schedules, and sharing of question links to students. The assessment is carried out on the day of the exam determined by the institute and students work from home at a predetermined time. Students can access and send answers on time (96,5%). The conclusion of this research is that the implementation of the online assessment at IAINU Kebumen can be followed by students according to the assessment indicators that have been targeted.